2023
DOI: 10.1007/s10528-023-10400-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Related to Immune Cells in Patients with COVID-19 Via Integrated Bioinformatics-Based Analysis

Abstract: COVID-19 has spread all over the world which poses a serious threat to social economic development and public health. Despite enormous progress has been made in the prevention and treatment of COVID-19, the specific mechanism and biomarker related to disease severity or prognosis have not been clarified yet. Our study intended to further explore the diagnostic markers of COVID-19 and their relationship with serum immunology by bioinformatics analysis. The datasets about COVID-19 were downloaded from the Gene E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This work suggests that PDCD6 functions as a negative regulator of cytosolic DNA-induced innate immune responses. Additionally, a recent study discovered that PDCD6 is significantly differentially expressed in normal individuals and COVID-19 patients, so it may be a diagnostic marker for COVID-19 (Chen et al, 2023).…”
Section: The Roles Of Pdcd6 In Innate Immunitymentioning
confidence: 99%
“…This work suggests that PDCD6 functions as a negative regulator of cytosolic DNA-induced innate immune responses. Additionally, a recent study discovered that PDCD6 is significantly differentially expressed in normal individuals and COVID-19 patients, so it may be a diagnostic marker for COVID-19 (Chen et al, 2023).…”
Section: The Roles Of Pdcd6 In Innate Immunitymentioning
confidence: 99%
“…CDC25A (Cell Division Cycle-25A) plays a crucial role in the cell cycle and apoptosis by dephosphorylating its substrates (69). mRNA expression of CDC25A has been reported to be downregulated in aging skeletal muscle (70) and up-regulated in COVID-19 (71). In COVID-19, CDC25A has been found to be closely associated with immune cell infiltration such as plasma cells, macrophages, T cells, dendritic cells and NK cells, and plays an important role in disease progression as a biomarker for COVID-19 diagnosis (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…mRNA expression of CDC25A has been reported to be downregulated in aging skeletal muscle (70) and up-regulated in COVID-19 (71). In COVID-19, CDC25A has been found to be closely associated with immune cell infiltration such as plasma cells, macrophages, T cells, dendritic cells and NK cells, and plays an important role in disease progression as a biomarker for COVID-19 diagnosis (71,72). It has been demonstrated that MYBL2 and BCL6 are significantly upregulated in SARS-CoV-2 infected patients (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…CDC25A (Cell Division Cycle-25A) plays a crucial role in the cell cycle and apoptosis by dephosphorylating its substrates (69). mRNA expression of CDC25A has been reported to be downregulated in aging skeletal muscle (70) and up-regulated in COVID-19 (71). In COVID-19, CDC25A has been found to be closely associated with immune cell infiltration such as plasma cells, macrophages, T cells, dendritic cells and NK cells, and plays an important role in disease progression as a biomarker for COVID-19 diagnosis (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…mRNA expression of CDC25A has been reported to be downregulated in aging skeletal muscle (70) and up-regulated in COVID-19 (71). In COVID-19, CDC25A has been found to be closely associated with immune cell infiltration such as plasma cells, macrophages, T cells, dendritic cells and NK cells, and plays an important role in disease progression as a biomarker for COVID-19 diagnosis (71,72). It has been demonstrated that MYBL2 and BCL6 are significantly upregulated in SARS-CoV-2 infected patients (73,74).…”
Section: Discussionmentioning
confidence: 99%